2011
DOI: 10.1002/jsfa.5544
|View full text |Cite
|
Sign up to set email alerts
|

Aloysia triphylla infusion protects rats against dextran sulfate sodium-induced colonic damage

Abstract: The results suggest that lemon verbena infusion partially protects rats against DSS-induced inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Inflammatory bowel diseases (IBDs), particularly ulcerative colitis, have been long related to increased burden of oxidative stress (Achitei et al, 2013;Koutroubakis et al, 2004;Rezaie, Parker, & Abdollahi, 2007). To this regard, multiple studies revealed that antioxidant/antiinflammatory herbal extracts could be effective in the management of IBDs symptoms, particularly those related to increased oxidative stress (Chung et al, 2007;Lenoir et al, 2012;Ma et al, 2018;Zhang, Ma, Gao, Sun, & Zhang, 2017). In this context, a preliminary preclinical study was performed in order to evaluate protective effects of devil's claw in IBDs.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Inflammatory bowel diseases (IBDs), particularly ulcerative colitis, have been long related to increased burden of oxidative stress (Achitei et al, 2013;Koutroubakis et al, 2004;Rezaie, Parker, & Abdollahi, 2007). To this regard, multiple studies revealed that antioxidant/antiinflammatory herbal extracts could be effective in the management of IBDs symptoms, particularly those related to increased oxidative stress (Chung et al, 2007;Lenoir et al, 2012;Ma et al, 2018;Zhang, Ma, Gao, Sun, & Zhang, 2017). In this context, a preliminary preclinical study was performed in order to evaluate protective effects of devil's claw in IBDs.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…The exploration of novel therapeutic methods is urgently needed. For exploring novel therapeutic methods of IBD, various studies have focused on the potential value of herbal extract, such as Scutellariae radix , Aloysia triphylla , Harpagophytum procumbens and Chamomile , and found that the herbal extracts have therapeutic effect in experimental model of IBD ( Chung et al, 2007 ; Lenoir et al, 2012 ; Menghini et al, 2016 ; Locatelli et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory bowel diseases (IBDs) are chronic disorders of the colonic mucosa (ulcerative colitis), whose etiology is strictly related to increased oxidative stress (Koutroubakis et al, 2004;Rezaie et al, 2007;Achitei et al, 2013). On the other hand, antioxidant/antiinflammatory herbal extracts were able to contrast oxidative stress-related IBD symptoms (Chung et al, 2007;Lenoir et al, 2012). Harpagophytum procumbens, traditionally known as devil's claw or Harpagophytum, is a plant species that has been long used for the treatment of inflammatory diseases, including degenerative rheumatoid arthritis, osteoarthritis and tendonitis (Chantre et al, 2000), kidney inflammation (Kaszkin et al, 2004) and heart disease (Circosta et al, 1984;Costa De Pasquale et al, 1985).…”
Section: Introductionmentioning
confidence: 99%